Becoming urban: State and migration in contemporary China. - Luo, Rumin (Kassel University Press, 2014)
With China s sky-rocketing economic growth since the late 1980 s, the mobility of its labor force has increased tremendously. In the early 21st century the number of internal migrants is approaching 300 million, corresponding to more than 20% of the country s population. This development has become a cause for political concern, highlighting significant issues in the social relations between settled communities and new migrants. This book examines in depth how institutional arrangements, in particular, the Hukou (Household Registration) system, influence the integration of migrants at their destinations. Under this unique Chinese settlement system, migrants are defined by their Hukou location to which they are allocated by birth or by later official permissions if they fulfill certain requirements. The primary research questions approached concern the economic, social, political and psychological integration of migrants in cities. They are answered on the basis of both quantitative and qualitative original primary data. The findings are impressive. Migrants show strong performances with regard to their integration into labor markets and their income levels. Nevertheless, they display significantly weaker performances in the area of social integration and political integration. Surprisingly no difference in integration at the psychological level could be found.
Keywords: Bevölkerungsentwicklung; Bevölkerungswanderung; Stadtwachstum; Landflucht; Arbeitsmigration; Binnenwanderung; Integration; Sozialbeziehung; Befragung; Wanderarbeiter